(untitled) (The International Journal for Scientific Research, 2026)
This research aims to study the impact of force majeure and unforeseen circumstances on contracts under the Saudi legal system, in light of recent economic and social developments and the exceptional crises that have affected the performance of contractual obligations worldwide. The research adopts a descriptive-analytical approach to examine relevant legal texts, Islamic jurisprudence principles, and judicial applications. The research reached several important findings, most notably: Force majeure leads to the absolute impossibility of performing contractual obligations, resulting in the termination of the obligation or rescission of the contract, whereas unforeseen circumstances merely make performance onerous, justifying judicial intervention to restore contractual balance. The research also confirmed that the Saudi legal system - particularly the Civil Transactions Law issued in 1444 AH - has achieved a precise balance between the principle of "pacta sunt servanda" (the contract is the law of the parties) and the principle of justice by taking into account exceptional circumstances. The research based its analysis on foundational Sharia principles such as "no harm and no reciprocating harm" (la darar wa la dirar), "hardship begets facility" (al-mashaqqah tajlib al-taysir), and "harm must be eliminated", illustrating the role of Saudi courts in applying these principles, especially during the COVID-19 pandemic. The research recommended the need to enhance legal texts, include explicit clauses in contracts to deal with exceptional circumstances, and promote a culture of renegotiation between parties.